Efficacy of the Fluorescein Tear Breakup Time Test in Dry Eye. Issue 1 (January 2020) - Paugh, Jerry R.; Tse, June; Nguyen, Tiffany; Sasai, Alan; Chen, Elaine; De Jesus, Melinda Thomas; Kwan, Justin; Nguyen, Andrew Loc; Farid, Marjan; Garg, Sumit; Jester, James V.
Abstract : Purpose: To examine the effects of volume and method on fluorescein tear breakup time (TBUT) values and to evaluate test efficacy in an independent sample free of selection bias. Methods: Subjects were assessed using a battery of dry eye tests (DETs). Efficacy study: Subjects were randomized to the DET, standard strip, and liquid NaFl on separate days. A masked examiner measured TBUTs from video recordings. Verification study: Subjects were investigated for efficacy using volumes of 5.0 and 2.0 μL mL of NaFl for TBUT. Results: Efficacy study: 46 subjects completed the study. Log-transformed TBUTs were significantly different, normal subjects versus dry subjects, for all 3 methods (all P values < 0.001). Area under the curves (AUCs), cut-points, sensitivity, and specificity were 1) DET: 0.873, 4.4 seconds, 0.97, and 0.67, respectively; 2) 2.0 mL: 0.901, 3.22 seconds, 0.90, and 0.87, respectively; and 3) standard strip: 0.912, 3.42 seconds, 0.97, and 0.80, respectively. Verification study: Data splitting analysis for the 2.0 μL data (n = 174 dry subjects and 97 normal subjects) generated an AUC of 0.917 and a cut-point of 6.05 seconds for a sensitivity of 0.87 and a specificity of 0.81. The 5.0 μL sample yielded an AUC of 0.940, with a sensitivity and specificity of 0.92 and 0.83, respectively, at a cut-point of 5.5 seconds. Conclusions: Little difference in TBUT was found using the 3 clinical methods with video recordings. Analysis using liquid NaFl suggests that the TBUT test has excellent diagnostic accuracy and that a cut-point of 5.3 to 6.0 seconds is the optimum to differentiate normals from persons with dry eye.